Penerapan Pola Agroforestri Berbasis Kelapa dan Pendapatan Petani di Desa Samuda, Kabupaten Halmahera Utara - Lewerissa, Ebedly; Budiadi, Budiadi; Hardiwinoto, Suryo; Subejo, Subejo (Universitas Pattimura, 2020)
This study aims to determine the application of agroforestry patterns and their contribution to the income of farmers in the village of Samuda, North Halmahera Regency. The research method used was a purposive sampling method, with 30 respondent farmers who had coconut-based agroforestry land. Data collection and analysis are done descriptively and quantitatively. The results showed that two patterns of agroforestry application, the Agrisilvikultur Tress Along with Borders pattern and the Agrisilvikultur Random Mixture pattern, we're able to make many ecological and economic contributions. From the ecological point of view, mixed agroforestry patterns can increase resistance to plant diseases, and economically, agroforestry patterns can increase farmers' average income. Completion of coconut-based agroforestry in the form of copra increased the average annual income of IDR 35,633,333.3/year and the average income from secondary crops by IDR. 1,249,637,500/year. While the average income from non-agroforestry products is IDR 34,550,000/year. Comparison of income and expenditure shows that the average income of farmers is greater than the expenditure, so the application of agroforestry patterns has a significant influence on the level of welfare of farmers in the study area.